Selection of one social network to support higher education teaching through computing with words - Veloz Morales, Dargel (2021)
Social networks have impacted society, to such an extent that in many occasions it is more important to be aware of them than any other application on the cell phone, tablet or laptop. On the other hand, the arrival of the covid-19 disease has also impacted the way students, teachers and the education system itself act. The present work aims to select the most suitable social network for higher education support, through computing with words, used to perform the process of computation and reasoning. In addition, the FLINTSTONES program is used to simulate the different models. Finally, the results achieved for each of the three social networks analyzed are presented: Telegram, WhatsApp and Facebook.